Importance of stimuli responsive confined space - Singh, Ashutosh Sharan; Simiran; Garg, Sonika (RSYN Proceedings, 2025)
Molecular behaviour changes drastically in a confined space in comparison to their corresponding bulk phase. A confined space also available to trap/encapsulate a guest molecule. In an artificial system, such confined space also termed as cavity formed through judicial choice of either only organic ligand (termed as capsule) or with suitable metal-ion (termed as metallacapsule). Molecular capsule formed by non-covalent interactions gets benefit of reversible assembly in response to an external stimulus through dynamic self-assembly. In this presentation we will discuss about encapsulation of notorious and toxic nitrate anion and their role in the formation and isolation of single isomer, formed by photochemical [2+2] cycloaddition reaction with mechanistic point of view.